Baroque & later paintings in the Ashmolean Museum - Whistler, Catherine (Modern Art Press, 2016)
Masterpieces by Nicolas Poussin, Claude Lorrain, Domenichino, Giambattista Tiepolo and Francesco Guardi feature in this detailed catalogue of 'Baroque and later paintings in the Ashmolean Museum'. The collection of Italian, French and Spanish works from about 1600 onwards was mainly formed in the late nineteenth and twentieth centuries, reflecting the interests of a University museum and its benefactors. Changing perceptions of art of the Baroque age can be traced in the histories of opinions and ownership that this catalogue provides